An alternatively activated macrophage marker CD163 in severely obese patients: the influence of very low-calorie diet and bariatric surgery - Cinkajzlová, A; Lacinová, Z; Kloučková, J; Kaválková, P; Trachta, P; Kosák, M; Krátký, J; Kasalický, M; DoleŽalová, K; Mráz, M; Haluzík, M (Physiological research, 2017)
CD163 is a marker of macrophages with anti-inflammatory properties and its soluble form (sCD163) is considered a prognostic predictor of several diseases including type 2 diabetes mellitus (T2DM). We explored sCD163 levels at baseline and after very low-calorie diet (VLCD) or bariatric surgery in 32 patients with obesity (20 undergoing VLCD and 12 bariatric surgery), 32 obese patients with T2DM (22 undergoing VLCD and 10 bariatric surgery), and 19 control subjects. We also assessed the changes of CD163 positive cells of monocyte-macrophage lineage in peripheral blood and subcutaneous adipose tissue (SAT) in subset of patients. Plasma sCD163 levels were increased in obese and T2DM subjects relative to control subjects (467.2+/-40.2 and 513.8+/-37.0 vs. 334.4+/-24.8 ng/ml, p=0.001) and decreased after both interventions. Obesity decreased percentage of CD163+CD14+ monocytes in peripheral blood compared to controls (78.9+/-1.48 vs. 86.2+/-1.31 %, p=0.003) and bariatric surgery decreased CD163+CD14+HLA-DR+ macrophages in SAT (19.4+/-2.32 vs. 11.3+/-0.90 %, p=0.004). Our data suggest that increased basal sCD163 levels are related to obesity and its metabolic complications. On the contrary, sCD163 or CD163 positive cell changes do not precisely reflect metabolic improvements after weight loss.
Keywords: Antigens, CD; obezita; Bariatric Surgery; antigen CD163; CD antigeny; Humans; kalorická restrikce; lidé středního věku; Caloric Restriction; Female; CD163 Antigen; makrofágy; dospělí; lidé; Biomarkers; Blood Glucose; receptory buněčného povrchu; Diabetes Mellitus, Type 2; Adult; biologické markery; ženské pohlaví; Male; Middle Aged; Receptors, Cell Surface; krevní glukóza; bariatrická chirurgie; antigeny diferenciační myelomonocytární; Obesity; Macrophages; mužské pohlaví; diabetes mellitus 2. typu; Antigens, Differentiation, Myelomonocytic